TINDAK TUTUR PADA ANAK-ANAK USIA 7 TAHUN 10 BULAN (Analisis Wacana) - Santoso, Joko (LP3M STAI DARUSSALAM LAMPUNG, 2015)
Events of speech act used by children to make requests to the partnersaid. Used speech acts using forms bemacam-wide in a communicationevent, the speakers did not always just mean to get something fromthe parner he said, but also to maintain good relations with partnerand he said it that interaction degan running smoothly.Found a request speech acts used by childern with a wide range, whichis not said directly to the target, there are 3 event with speech andspeech acts reasons / argument there are three event said. Based onthe authorâs observations, the authors found an indirect speech actwith the mode of seduction and threats.Keywords: Speech, Child.